Comparison between the effects of acetaminophen, dexmedetomidine, and normal saline infusion on pain severity after cataract surgery - Dariush Moradi Farsani; Seyed Ali-Akbar Mortazavi; Sanaz Masjedi; Sayed Morteza Heidari; Behzad Nazemroaya (Advanced Biomedical Research, 2022)
Background: Cataract surgery is one of the most common eye surgeries, which is currently performed under topical anesthesia using sedative medications. Dexmedetomidine and acetaminophen are good candidates for analgesia in other circumstances, however, this study aimed to evaluate the effect of dexmedetomidine or acetaminophen infusion and normal saline (NS) alone compared with the control group on the severity of pain in cataract surgery. Materials and Methods: In this parallel randomized controlled clinical trial, the effect of dexmedetomidine or acetaminophen infusion and NS on level of pain, vital signs, recovery status, and surgeon satisfaction during cataract surgery were assessed. One hundred and thirty-five patients between the age of 50–80 years undergoing cataract surgery were recruited on a consecutive basis and randomized into three groups receiving acetaminophen (15 mg/kg), dexmedetomidine (0.5 μgr/kg), and NS. Baseline vital signs, blood pressure, arterial oxygen saturation, respiratory and heart rate at certain time-points including the start of surgery, 5, 10, and 15 min after surgery, after arrival to the recovery room, 20, 40, 60 min after recovery were measured. Pain intensity and drugs side effects were also recorded after surgery. Results: Level of respiratory depression was higher in patients receiving dexmedetomidine. Heart rate and oxygen saturation percentage had no significant differences in the three groups as well as pain intensity. Conclusions: Acetaminophen was as effective as dexmedetomidine with lower side effects and higher surgeons' satisfaction, without any interference with cardiovascular and respiratory parameters. Acetaminophen infusion should be considered as an acceptable analgesic drug for cataract surgery.